Vocabulary teaching strategies used by tesl trainees during teaching practice - Esther, Litad Padan. (Universiti Malaysia Sarawak, UNIMAS, 2009)
Increasing v ocabulary is one part of language skills. This project seeks to find the Vocabulary Teaching strategies used and fre quently used by the TESL Trainees during Teaching Practice. It also tries to look into the strategies frequently used in teaching comprehension text and literature text. The method used for the data collection is a checklist that to find out the vocabular y teaching strategies from TESL trainees lesson plan . They have no teaching experience during their Teaching Practice.